THE UNDERLYING PRINCIPLES OF SUSILO BAMBANG YUDHOYONO‘S THOUGHT PATTERNS IN HIS ENGLISH SPEECH TEXTS - ningsih, Sulistya (Jurnal Pendidikan Bahasa dan Sastra, 2014)
The underlying principles of thought patterns as shown in SBY's English Speeches Texts are made because there are different responses from the public, a part of public praise that SBY is a good president, and others claim and criticize him that  he is slow (Djalal, 2007: forward page). This title so far has not been investigated. This research was aimed at finding out:  the underlying principles of SBY’s thought patterns in his English Speech Texts related to Javanese philosophy. This research is qualitative. The data selected from SBY’s speech Texts were analyzed using semantic and pragmastylistic theory then were related to Javanese philosophy. The findings are the underlying principles of SBY’s thought patterns based on Javanese philosophy manifested in his English Speech Texts are: first is Memayu Hayuning Bawana, Ambrasta dur Hangkara means to reach safety, peace, happiness and well-being of the world and its contents, to keep the world maintained and harmony. Second, Rukun agawe santosa crah agawe bubrah  means to build the condition of harmony, and avoid conflict, because conflict can be harmful to both parties. Third, tepa selira means keep thinking not to offend others or lighten the burdens of others, tolerance. Fourth is ana rembug becik dirembug means thru negotiations can avoid conflict and achieve cooperation, safety, peace and prosperity. In sum, the world peace can be reached thru discussions without war, soft powers.